107 Secondary intracranial hypertension in nephropathic cystinosis. Issue 12 (14th November 2019) - Harijanto, Chloe; Pegg, Emily; Biswas, Sumito; Lavin, Tim
Abstract : A 21-year-old woman presented with bilateral papilloedema and a 2-week history of high-pressure headaches. Medical history was remarkable for Infantile Cystinosis and a renal transplant. Her Body Mass Index was 26.7 kg/m2. Visual acuity (VA) was 6/12 in the left eye and 6/6 in the right. Cerebrospinal Fluid (CSF) opening pressure was 30cmH20 in the left decubitus position. Following lumbar puncture and Acetazolamide 250 mg bd, VA improved but the latter was stopped due to renal side effects. She was asymptomatic on Topiramate 50 mg bd. VA was 6/6 bilaterally, with decreased optic disc swelling on Optical Coherence Tomography and a normal CSF opening pressure. Discussion: Infantile Cystinosis is a rare autosomal recessive lysosomal storage disease where multisystem accumulation of cysteine leads to renal failure, hypothyroidism and corneal deposits. Intracranial Hypertension occurs in around 5% of patients with cystinosis (Dogulu 2004). Meningeal cysteine accumulation could reduce CSF absorption by the arachnoid villi. Other risk factors include renal transplant and immunosuppressant therapy. Neurologists should be aware of this rare but important complication of cystinosis. Low dose topiramate demonstrated benefit here and lacks the diuretic effects of acetazolamide. Early shunting or optic nerve decompression should be considered in severe cases.